Lei 13.415/2017: impactos no ensino médio técnico sob a ótica de coordenadores de cursos profissionalizantes do IFPR - Harmel, Ana Raquel (2019)
In February 2017 Law no. 13,415 / 2017 was sanctioned, known as the new High School Act, which instituted the Policy for the Promotion of the Implementation of High School Schools in Integral Time. In view of this new reality, that brings changes to the political-pedagogical proposals, as well as to the teaching-learning process, this research had as objective to identify what the coordinators of the technical courses of the High School of a federal public institution of Paraná know and how they evaluate the impact of the changes brought by said Law to vocational technical education. It is characterized as an applied, descriptive, qualitative and quantitative research. Participated 20 coordinators of technical courses of the High School of the Federal Institute of Paraná (IFPR). Data collection was done by e-mail, and consisted of a questionnaire containing sociodemographic data and six open-ended questions about knowledge of the text of the new Law, positive and negative impacts of the Law on Higher Education, and the teaching and learning. Responses were submitted to the content analysis of Bardin (1977). The results showed that the coordinators believe that the current technical training of the Secondary School allows the egress the necessary preparation to exercise a profession; show knowledge about Law no. 13.415 / 2017 regarding the form of offer of the disciplines, evaluation method, alteration of the workload and offer of training itineraries; indicate as positive aspects a more specific formation, enabling a better targeting of the student along its formation and as negative the lack of physical structure and personnel to ensure the effectiveness of the proposals of the Law with respect to the full time envisaged; they consider that there will be no significant changes in the learning process of the courses they coordinate, since the technical disciplines offered will tend to be maintained; however, they have doubts as to whether or not the impacts are different for the IFPR, than for other educational institutions, and this uncertainty is partly attributed to the lack of discussion on the subject. It is concluded that because it is a recent document, it is foreseeable that there are doubts and inquiries about its content and its applicability, but in general, the coordinators have a superficial knowledge of Law no. 13,415 / 2017, and their contributions constitute material for future research, specifically those inherent in the consequences of this fragile knowledge of a normalization that affects a considerable number of young people.